Emotional Intelligence and its Relationship with Future ‎Anxiety among a Sample of Orphan and Unknown ‎Descent Children - Gazo, Ahmad (Jordan Journal of Educational Sciences, 2020)
The current study aimed at investigating the level of emotional intelligence and future anxiety among a sample of orphans and unknown descent children, and examine the significant differences in emotional intelligence and future anxiety due to gender and child characteristics (orphan and unknown descent) variables, as well as to examine the correlation relationship between emotional intelligence and future anxiety. The study sample consisted of (206) orphan and unknown descent children, chosen by the convenient sampling method. The results of the study showed that the level of emotional intelligence among orphan and unknown descent children was high, and the level of future anxiety among orphan and unknown descent children was moderate. The results also showed no statistically significant differences in the level of emotional intelligence and its subscales, due to child characteristics (orphan and unknown descent), and that there were statistically significant differences in the level of emotional subscales: Managing others’ emotion, and utilization emotion, due to gender, in favor of female students and there were statistically significant differences in the level of future anxiety and its subscale due to gender, in favor of female students, but no statistically significant differences in the level of future anxiety and its subscale due to child characteristics (orphan and unknown descent). The results of the study also showed a negative correlation between emotional intelligence and future anxiety.